2017
DOI: 10.1021/acs.chemrestox.7b00037
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of Chemicals Binding to Aromatase with Machine Learning Methods

Abstract: Environmental chemicals may affect endocrine systems through multiple mechanisms, one of which is via effects on aromatase (also known as CYP19A1), an enzyme critical for maintaining the normal balance of estrogens and androgens in the body. Therefore, rapid and efficient identification of aromatase-related endocrine disrupting chemicals (EDCs) is important for toxicology and environment risk assessment. In this study, on the basis of the Tox21 10K compound library, in silico classification models for predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…In our model, MLP contained two hidden layers, each consisting of 128 neurons, with relu as the activation function and learning rate being 0.001. In addition, we searched the batch size as 50, 100, 200, and 300 as the potential parameter by using grid search written in Python scripts. Consensus classifier model: As mentioned in previous studies, the consensus classifier methods combining multiple well‐performed single classifier models had a better prediction accuracy than each single classifier model . Thus, the construction of this classifier used in our study consisted of a three‐layer perceptron neural network of which the classified results are from single models.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model, MLP contained two hidden layers, each consisting of 128 neurons, with relu as the activation function and learning rate being 0.001. In addition, we searched the batch size as 50, 100, 200, and 300 as the potential parameter by using grid search written in Python scripts. Consensus classifier model: As mentioned in previous studies, the consensus classifier methods combining multiple well‐performed single classifier models had a better prediction accuracy than each single classifier model . Thus, the construction of this classifier used in our study consisted of a three‐layer perceptron neural network of which the classified results are from single models.…”
Section: Methodsmentioning
confidence: 99%
“…Consensus classifier model: As mentioned in previous studies, the consensus classifier methods combining multiple well‐performed single classifier models had a better prediction accuracy than each single classifier model . Thus, the construction of this classifier used in our study consisted of a three‐layer perceptron neural network of which the classified results are from single models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, to enhance performance of prediction models, combination of these algorithms is applied. We developed a combined method using an artificial neural network (ANN) model to generate the final combination decision probability, which showed that the combined methods would be superior to “single” methods (Cheng et al, 2011b ; Du et al, 2017 ; Sun et al, 2017 ).…”
Section: Model Building With Machine Learning Methodsmentioning
confidence: 99%
“…Based on the well-defined structural fragments dictionary, MACCS molecular fingerprint is full of structural information [ 33 ]. In previous studies, MACCS and PubChem fingerprints had also been proven to outperform other fingerprints in classifier models [ 33 , 34 ]. By contrast, the Est fingerprint performed worst when the same machine learning methods were used.…”
Section: Resultsmentioning
confidence: 99%